Fisheries Supply Chain Model Using Structural Equation Modeling (SEM) to Support the SDGs in the Fisheries Industry - Indra Jaya Kusuma Wardana; Arie Wahyu Prananta; I Wayan Suyadnya; Iqbal Mahcfud Fauzi (Jurnal Penelitian Pendidikan IPA, 2025)
The global fisheries supply chain faces challenges related to data integrity, product traceability, and distribution inequality, which impact the achievement of the Sustainable Development Goals (SDGs), particularly SDG 2 (Zero Hunger) and SDG 12 (Responsible Consumption and Production). The main challenges are rooted in three critical pillars: data integrity, product traceability, and distribution inequality. The lack of accurate and transparent fishing data opens up opportunities for illegal, unreported, and unregulated (IUU) fishing, which is seriously depleting fish stocks. The global fisheries supply chain is a complex and vital network, providing a vital source of protein for billions of people worldwide. However, this complex system faces a series of fundamental challenges that threaten environmental sustainability and social equity, and hinder global efforts to achieve the Sustainable Development Goals (SDGs). Blockchain is a disruptive technology that offers transparency and accountability in the supply chain system. This study aims to examine the impact of blockchain technology adoption on food security through fisheries supply chain efficiency, using the Structural Equation Modeling (SEM) method. The results indicate that blockchain has a significant impact on improving logistics efficiency, product traceability, and consumer trust, which indirectly strengthens national food security. Recommendations are directed at synergy between industry players and the government to accelerate blockchain-based supply chain digitalization.